Cost-Effectiveness analisys on the implementation of clinical pathway of pediatric treatment for dengue hemorrhagic fever in PKU Muhammadiyah Hospital Yogyakarta - Riana Prastiwi Handayani; Dyah Ariyani Perwitasari; Didik Setiawan; Auliya Abdurrohim Suwantika (Pharmaciana, 2020)
Dengue Hemorrhagic Fever (DHF) remains a concerning world problem especially in Indonesia. This problem particularly deals with therapeutic management of hospitalized children requiring DHF treatment. The current practice of therapeutic management is not in accordance with the standard therapeutic management, which increases the treatment cost. On this account, the application of a clinical pathway is expected to minimize the treatment cost and reduce the length of stay (LoS). However, prior to its the application, it is necessary to analyze the cost effectiveness of the implementation of clinical pathway on pediatric DHF treatment in PKU Muhammadiyah Hospital, Yogyakarta. A retrospective cohort study and cost-effectiveness analysis were applied in this study by considering hospitalâ€™s (provider) perspective. Two groups (conform to clinical pathway and not conform to clinical pathway group) were involved in this study. Data of direct medical costs of pediatric DHF treatment, which were suitable with clinical pathways and LoS during 2016-2017 period, were collected in this study. The Incremental Cost Effectiveness Ratio (ICER) between both groups and the Risk Ratio (RR) were calculated as the outcome. Â The result confirmed that from 200 patients involved, the treatments of 138 patients (69 %) and 62 patients (31%) were included in the conformed to clinical pathway and not conformed to clinical pathway groups, respectively, with p value of 0,000 and RR of 1,58. The average costs were calculated to be Rp 1.144.024 + Rp 556.372 and Rp 1.989.723 + Rp 1.296.899 for conformity to clinical pathway and non-conformity to clinical pathway groups, respectively. The ICER was calculated to be Rp 826.917. In conclusion, the implementation of clinical pathway on pediatric DHF treatment in PKU Muhammadiyah Hospital, Yogyakarta could reduce LoS and the possibility of having a shorter LoS of up to 1.58 times, it can save cost of Rp 919.238 per one-day reduction in LoS.